2014
DOI: 10.1002/ajim.22317
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors at work and sickness absence: Results from the French National SUMER Survey

Abstract: This study highlights the importance of psychosocial work factors as risk factors of sickness absence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 38 publications
5
48
2
4
Order By: Relevance
“…This finding is in accordance to the findings of studies on risk factors for sick leave, where psychosocial working conditions were identified as risk factors for sickness absence. 5,19,20 Nevertheless, in contrast to the findings of most previous studies, we found the strongest associations between job demands and sickness absence and not job control and sickness absence. 19,21 An explanation for this discrepancy may be that relatively few studies are of general working populations.…”
Section: Previous Literature and Possible Mechanismscontrasting
confidence: 99%
“…This finding is in accordance to the findings of studies on risk factors for sick leave, where psychosocial working conditions were identified as risk factors for sickness absence. 5,19,20 Nevertheless, in contrast to the findings of most previous studies, we found the strongest associations between job demands and sickness absence and not job control and sickness absence. 19,21 An explanation for this discrepancy may be that relatively few studies are of general working populations.…”
Section: Previous Literature and Possible Mechanismscontrasting
confidence: 99%
“…In the SUMER survey, which aimed to evaluate occupational hazards in nearly 50,000 employees, caregivers were 40 years on average and 88% were women. The occupational distribution of caregivers in our study is comparable to those of the SUMER study: 65% of caregivers were nursing assistants or medico‐ psychological auxiliary staff, 22% homecare assistant and 12% nurses in our study as compared to 59%, 21% and 16% in the SUMER survey, respectively (Lesuffleur, Chastang, Sandret, & Niedhammer, ).…”
Section: Discussionsupporting
confidence: 80%
“…In Cad. Saúde Pública 2019; 35 Sup 1:e00081118 addition, despite the limited existing literature, long working hours alone had so far been negatively associated with sickness absence in both women and men 25,26 .…”
Section: Discussionmentioning
confidence: 99%